2016
DOI: 10.3390/molecules21030376
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized Bed Membrane Reactors for Ultra Pure H2 Production—A Step forward towards Commercialization

Abstract: Abstract:In this research the performance of a fluidized bed membrane reactor for high temperature water gas shift and its long term stability was investigated to provide a proof-of-concept of the new system at lab scale. A demonstration unit with a capacity of 1 Nm 3 /h of ultra-pure H 2 was designed, built and operated over 900 h of continuous work. Firstly, the performance of the membranes were investigated at different inlet gas compositions and at different temperatures and H 2 partial pressure difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…The pattern looks like overlapping grains, like a fish scale. As mentioned in the discussion of the permeation results, the main increase in nitrogen permeation was found to occur between 450 • C and 500 • C. Helmi et al [37] showed that no significant surface effects were visible after fluidization at 400 • C. Therefore, it is expected that the main surface deformation took place between 450 • C and 500 • C. It is expected that a combination of operation at the temperatures above 450 • C, and the scouring action of the fluidized particles, results in an increase in surface energy. Since the palladium layer is ductile and the hardness of the palladium decreases with temperature, the increased surface energy could allow ductile deformation of the PdAg layer.…”
Section: Sem Analysismentioning
confidence: 79%
“…The pattern looks like overlapping grains, like a fish scale. As mentioned in the discussion of the permeation results, the main increase in nitrogen permeation was found to occur between 450 • C and 500 • C. Helmi et al [37] showed that no significant surface effects were visible after fluidization at 400 • C. Therefore, it is expected that the main surface deformation took place between 450 • C and 500 • C. It is expected that a combination of operation at the temperatures above 450 • C, and the scouring action of the fluidized particles, results in an increase in surface energy. Since the palladium layer is ductile and the hardness of the palladium decreases with temperature, the increased surface energy could allow ductile deformation of the PdAg layer.…”
Section: Sem Analysismentioning
confidence: 79%
“…The tested membranes were: ceramic supported Pd-Ag membrane (4 µm thick), metallic supported Pd-Ag membrane (4-5 µm thick) and ultra-thin Pd-Ag membranes (~1 µm thick). The setup consists of three main sections: a feed section, a membrane module section and an analysis section [25,30]. At the feed section mass flow controllers from BROOKS b.v. were used to set the desired gas composition (e.g.…”
Section: Long-term Stability Testmentioning
confidence: 99%
“…The tests results are presented in Section 3.1.2. In DEMCAMER project, the performance of a fluidized bed WGS membrane reactor (FBMR) using five ceramic supported Pd-Ag membranes (4-5 µm) has been investigated and compared with the performance of a conventional fluidized bed reactor (FBR) [30]. The catalyst was 2 wt% Pt loading impregnated onto 80-200 µm size alumina particles.…”
Section: H2s Exposure Testmentioning
confidence: 99%
“…It is widely accepted that fluidized bed membrane reactors can outperform packed bed membrane reactor configurations due to their better mass and heat transfer properties [3]. Most of the literature on this topic has been devoted to provide a proof-of-concept at lab-scale or to monitor the long term performance of the membranes at different operating conditions and fluidization velocities [4].…”
Section: Introductionmentioning
confidence: 99%